Espaçamento, adubação nitrogenada e potássica em cobertura na cultura do milho - Deparis, Gelavir Antonio (2006)
This work had the objective of evaluate the effect of reduction of the spacement between lines and the nitrogen and potassium fertilization in covering, efficiency of absorption of nutrients, productivity, production components and changeable biometrics in the corn culture, hybrid Penta, and early cycle. The experiment was installed in Cascavel, PR in the area of Centro Tecnológico Coopavel (CTC), in the agricultural year of 2004/05, in eutroferric Red Latosol, no-tillage system. It was studied three spacements between lines (0,45; 0,67 e 0,90 m), with a population of 55.000 plants ha 1, appropriated to each spacement, with four repetition. The experimental delimitation consisted of blocks whole casualized, arranged in subdivided portions. It was used 13 combinations of seven nitrogen doses (8; 20; 40; 80; 120; 140 e 152 kg ha 1 de N), as ammonium sulfate, with seven potassium doses (3; 7,5; 15; 30; 45; 52,5 e 57 kg ha 1 de K2O), as potassium chloride. These treatments were allocated in the subportions and in the main portion were allocated the spacements adding 39 treatments. The reduction of spacement between lines of 0,90 m to 0,45 m maintaining the same population in each area proportioned the increase of whole dry biomass production and also more efficiency in the absorption of nitrogen and potassium and more efficiency in using N and K in the grain, in consequence of better spatial distribution of the plants. The variations in the interlines spacing of 0,45; 0,67 e 0,90 m, maintaining the same population of plants did not resulted in variations in the productivity of grains for corn. It was verified a linear increase in the productivity and dry biomass production in the air part to the of 152 kg ha-1 of in covering. The fertilization with potassium proportioned increase of the production of dry biomass of the air part, but it did not influenced in the productivity. Doses above 80 kg ha-1 of N and 30 kg ha 1 of K2O, resulted in less using efficiency of nitrogen and potassium fertilizers